2020
DOI: 10.1088/1748-9326/ab7df9
|View full text |Cite
|
Sign up to set email alerts
|

Comparative assessment of environmental variables and machine learning algorithms for maize yield prediction in the US Midwest

Abstract: Crop yield estimates over large areas are conventionally made using weather observations, but a comprehensive understanding of the effects of various environmental indicators, observation frequency, and the choice of prediction algorithm remains elusive. Here we present a thorough assessment of county-level maize yield prediction in U.S. Midwest using six statistical/machine learning algorithms (Lasso, Support Vector Regressor, Random Forest, XGBoost, Long-short term memory (LSTM), and Convolutional Neural Net… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
59
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 134 publications
(95 citation statements)
references
References 58 publications
5
59
0
Order By: Relevance
“…Despite this, DA SM+CC still significantly improves yield estimates in almost all years (nRMSE = 15.74%) with good accuracy (Jamieson et al, 1991). The lead time and prediction accuracy are comparable to other yield prediction studies (Peng et al, 2018;Kang et al, 2020). Here only the assimilation of data within 90 days after planting (around 3 months before harvest) was tested.…”
Section: Potential For Yield Prediction Using Remote Sensingmentioning
confidence: 66%
“…Despite this, DA SM+CC still significantly improves yield estimates in almost all years (nRMSE = 15.74%) with good accuracy (Jamieson et al, 1991). The lead time and prediction accuracy are comparable to other yield prediction studies (Peng et al, 2018;Kang et al, 2020). Here only the assimilation of data within 90 days after planting (around 3 months before harvest) was tested.…”
Section: Potential For Yield Prediction Using Remote Sensingmentioning
confidence: 66%
“…Recently, several studies have examined the performance of machine learning algorithms such as Support Vector Machine (SVM), Random Forest (RF), eXtreme Gradient Boost (XGBoost), Artificial Neural Network (ANN) and Long-Short Term Memory (LSTM) for yield forecasting at county or province scales. They have used multi-source data as predictors, and they found that the non-linear machine learning methods showed a better performance for yield forecasting than the linear approach [48][49][50][51][52][53][54]. Schwalbert et al [55] have used different machine learning algorithms (linear regression, RF and LSTM) to predict soybean yield at the municipality level in Brazil by using remote sensing data (NDVI, EVI, LST) and precipitation as predictors.…”
Section: Introductionmentioning
confidence: 99%
“…Understanding how different factors (e.g., climate, soil, managements) affect crop yield has critical values to scientific research and practical applications. Identifying and quantifying the relationships between crop yield and various factors allows for better ways to close the yield gap, increase yield potentials (Lobell et al, 2009;van Ittersum et al, 2013), and improve the predictive capability of crop yield for both short-run commodity market and long-term climate change adaptation (Schlenker and Roberts, 2009;Cai et al, 2017;Peng et al, 2018;Li et al, 2019;Kang et al, 2020). The U.S. Corn Belt produces about ∼30% of the total global corn production and plays the most critical role in the global corn export.…”
Section: Introductionmentioning
confidence: 99%
“…How environment and managements affect corn yield is a classic question that has been studied extensively by agronomists, plant biologists, economists, and recently earth system scientists (Cassman, 1999;Al-Kaisi and Yin, 2003;Kucharik, 2003;Schlenker and Roberts, 2009;Subedi and Ma, 2009;Lobell et al, 2014;Kang et al, 2020). However, there are still a few gaps.…”
Section: Introductionmentioning
confidence: 99%